Effects of Waiting Room and Feline Facial Pheromone Experience on Blood Pressure in Cats - Van Vertloo, Laura R.; Carnevale, Joyce M.; Parsons, Rebecca L.; Rosburg, Meghann; Millman, Suzanne T. (Frontiers in Veterinary Science, 2021)
Obtaining accurate blood pressure measurements in cats is challenging due to the stressful nature of clinic visits. The objective of this study was to evaluate the effects of veterinary clinic waiting experiences and a feline pheromone spray on blood pressure in the cat. We hypothesized that reduced stress associated with bypassing the waiting room and use of synthetic feline facial pheromone (FFP) spray would result in lower blood pressure. A 2x2 factorial design involved two rooms and two FFP treatments. Thirty-nine healthy adult cats were recruited and were systematically assigned to four treatment combinations administered over four visits in 2016 and 2017. Cats were kept in the hospital waiting room or were taken directly to the exam room, with or without FFP treatment. All cats were then acclimated to the exam room for an additional 10 minutes, where vocalizations were recorded manually, before blood pressure measurements were collected using Doppler ultrasonography. Data were analyzed using generalized linear mixed models, with room x FFP interaction, visit, sex and trial year in the model. There was no significant effect of waiting room by FFP interaction on blood pressure (p=0.95). Mean blood pressure was significantly higher at visit 1 than visits 2 and 4 (p<0.01), but higher at visit 3 than visit 2 (p=0.02). Mean blood pressure was higher in males (p=0.01), and males were more likely to be categorized as borderline hypertensive/hypertensive or severely hypertensive (p=0.01). Number of vocalizations was significantly associated with waiting room by FFP interactions (p<0.01), with fewer vocalizations associated with bypassing the waiting room and when FFP was provided. In conclusion, although we found some behavioral evidence supporting stress reduction when feline patients bypass the waiting room and are provided with FFP, these interventions did not result in lower blood pressure in a clinical setting.